Edukasi Asi Eksklusif Pada Ibu untuk Membantu Penurunan Kasus Stunting di Kelurahan Kedungmundu - Khasanah, Umi; Ichtiarsi, Sherkia; ., Prakasiwi; Lutfitasari, Ariyani; ., Novita; ., Nining (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2023)
One of the goals of the SDGs (Sustainable Development Goals) program is to end all forms of malnutrition with a strategic plan (renstra) to increase the percentage of babies less than 6 months who get exclusive breastfeeding. The coverage of exclusive breastfeeding in Semarang regency/city has not yet reached the national target because it is still at 55.4%. The low coverage of exclusive breastfeeding in infants is caused by many factors. Saltu Saltu Saltu Saluaryal which can be done to increase knowledge, awareness, and motivation to provide ASI by providing counseling with health education and about exclusive breastfeeding. Based on these conditions, this Community Service aims to increase the knowledge of mothers and the scope of breastfeeding. The method used is counseling and education about the benefits of breastfeeding and comfortable breastfeeding. The result of this activity is to increase the rate of breastfeeding for infants which is one way to reduce stunting rates and increase knowledge about breastfeeding and breastfeeding.